(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article is based on the scientific research of the essence and regulatory legal bases of investment activity, the conditions and factors of increasing investment activity in small industrial zones, the study of foreign experiences of increasing investment activity in canoe zones and the consideration of the possibilities of use.